Elements of photogrammetry with applications in GIS - Wolf, Paul R. (McGraw-Hill, 2000)
Introduction - Principles of photography and imaging - Cameras and other imaging devices - Image measurements and refinements - Objet space coordinate systems - Vertical photographs - Stereoscopic viewing - Stereoscopic parallax - Elementary methods of planimetric mapping for GIS - Tilted photographs - Introduction to analytical photogrammetry - Stereoscopic plotting instruments - Topographic mapping and spatial data collection - Fundamental principles of digital image processing - Principles of softcopy photogrammetry - Ground control for aerial photogrammetry - Aerotriangulation - Project planning - Terrestrial and cose-range photogrammetry - Introduction to geographic information systems - Photogrammetric applications in GIS - Appendices.